KELAYAKAN UJI VALIDASI AHLI MEDIA BERMAIN PUZZLE STIK SIRAH NABAWIYAH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK TK (Universitas PGRI Semarang, 2022)
Learning media is a supporter of learning success. The learning media developed in this study were playing media for early childhood, Puzzle sticks sirah nabawiyah to improve the early reading skills of kindergarten age children. Innovative and interesting media can increase children's interest in learning, especially in early childhood development, where children learn from concrete objects first in the learning process. With the principle of learning while playing and playing while learning, a new product was developed in the form of a stick puzzle that has the content of the story of the sirah nabawiyah. A story of the journey of Rasulullah SAW from the time he was born until he died leaving a very valuable legacy, the Qur'an and the sunnah. Therefore, this study aims to develop a media for playing puzzle sticks sirah nabawiyah to improve the reading ability of kindergarten age children. This play media was developed using the Borg and Gall development model (RnD) which was shortened to 8 steps due to time and cost constraints. Consists of the initial research phase, planning, initial draft development, expert validation test, revision of validation test, limited trial, revision and refinement of product of limited trial and wide usage trial. This paper specifically describes in detail at the expert validation test stage, which describes the feasibility of the graphic design aspects of media, materials and puzzle language from the validator. Based on the validation results from media, material and language experts, it shows that the Sirah nabawiyah stick puzzle is suitable for use in the field. With a percentage value of media experts reaching 93%, material experts 95% and linguists 90%.